The Influence of Work Motivation and Work Discipline on Employee Productivity in the Garment Industry of PT. Sumber Bintang Rejeki - Fau, Tesa Fincecia; Dewi, Idah Kusuma (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This article analyzes the influence of work motivation and discipline on employee productivity at PT. Sumber Bintang Rejeki. The problem is focused on how these two independent variables simultaneously or partially affect the level of employee productivity. To approach this problem, theoretical references regarding work motivation and work discipline are used. Data were collected through a survey using a questionnaire given to 100 respondents, then analyzed quantitatively using the multiple linear regression method using SPSS software. This study concludes that work motivation and work discipline simultaneously have a significant influence on employee productivity, with a contribution of 55.6% (R Square = 0.556). Partially, work discipline has a more dominant influence with a ? coefficient of 0.375 compared to work motivation with a ? coefficient of 0.096. The dominance of work discipline in increasing productivity can be associated with the role of compliance with rules, punctuality, and consistency in completing tasks that are more directly related to achieving work targets compared to motivational factors that are more subjective and vary between individuals. The implications of these findings indicate that companies need to strengthen the culture of work discipline through stricter supervision, the implementation of a clear reward and punishment system, and leadership training for managers to ensure consistency of work standards. In addition, improving work motivation programs is also needed through the provision of incentives, career development, and the creation of a more supportive work environment. With these steps, it is hoped that employee productivity can increase sustainably. The limitations of this study include the scope, which is only limited to one company, so the results cannot necessarily be generalized to other industries. In addition, other variables that can also affect productivity, such as work environment and leadership style, are not included in this research model. Therefore, further research is recommended to consider additional variables and expand the scope of the industry so that the results obtained are more comprehensive.